Effects of Three Pesticides on the Earthworm Lumbricus terrestris Gut Microbiota - Astaykina, Angelika; Streletskii, Rostislav; Maslov, Mikhail; Krasnov, George; Gorbatov, Victor (Frontiers in Microbiology, 2022)
Earthworms play a vital role in the terrestrial ecosystem functioning and maintenance of soil fertility. However, many pesticides, for example, imidacloprid, benomyl, and metribuzin that are world-widely used in agriculture, may be potentially dangerous to earthworms. At the same time, standard tests for pesticides acute and chronic toxicity do not reflect all aspects of their negative impact and might not be enough sensitive for effective assessment. In this paper we studied the effects of non-lethal concentrations of imidacloprid, benomyl, and metribuzin on the gut bacterial community of Lumbricus terrestris using high-throughput sequencing approach. We found that pesticides reduced the total bacterial diversity in the earthworm’s gut even at the recommended application rate. Under the applied pesticides, the structure of the gut prokaryotic community underwent changes in the relative abundance of the phyla Proteobacteria, Actinobacteria, Acidobacteria, Planctomyces, Verrucomicrobia, and Cyanobacteria, as well as the genera Haliangium, Gaiella, Paenisporosarcina, Oryzihumus, Candidatus Udaeobacter, and Aquisphaera. Moreover,the pesticides affected the abundance of Verminephrobacter - the earthworms’ nephridia specific symbionts. In general, the negative impact of pesticides on bacterial biodiversity was significant even under pesticides content, which was much lower than their acute and chronic toxicity values for the earthworms. These results highlighted the fact that the earthworm’s gut microbial community is highly sensitive to soil contamination with pesticides. Therefore, such examination should be included in the pesticide risk assessment protocols.